PRODAK MAKANAN NOUGAT Pengaruh Strategi pemasaran terhadap banyaknya penjualan online pada produk nougat marshmallow - Nurul af'idah (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
Marketing strategy is an important thing to pay attention to in a business, marketing strategy has a big share in the quantity of sales on the product. Marketing strategies not only encourage consumers to add products to their shopping carts, but also ensure that buyers recognize the products offered, review them, and buy products repeatedly. This research uses descriptive qualitative research methods. The data collection techniques used were direct observation, interviews, library research, and documentation. The result of the research activity is the creation of a digital marketing strategy through online promotions such as Facebook, Instagram, and marketplaces (Sohpee, Lazada, Tokopedia). This is expected to be utilized as widely as possible in order to expand its sales reach, increase the number of consumers, increase sales, introduce its products to the wider community and make content about the sale of marshmallow nougat food products more creative on social media sites.